Corporate Governance Country Assessment : Croatia - World Bank (Washington, DC, 2014)
This report assesses Croatia's corporate governance policy framework for publicly traded companies. It highlights recent improvements in corporate governance regulation, makes policy recommendations, and provides investors with a benchmark against which to measure corporate governance in Croatia. It is an update of the 2001 corporate governance Report on the Observance of Standards and Codes (ROSC). Croatia has experienced rapid and substantial reform over the last decade. New institutions have been created and the roles of private ownership and market forces have expanded. This rapid pace of reform has continued to meet the various requirements for membership in the European Union (EU). Since the 2001 ROSC there have been substantial legal and regulatory changes, many of which address shortcomings identified in the 2001 assessment. Since 2001, Croatia has undertaken substantial legal and regulatory change that has led to a number of improvements in the framework for corporate governance. The two stock exchanges were recently merged and a code of corporate governance introduced. Reform continues as Croatia works towards joining the EU. The real economy has also performed well, valuations have risen rapidly, and investment fund assets are growing strongly.